al-Lughah al-‘Arabīyah Lughat Tawāṣul al-Mushtarak bayn al-Shu‘ūb: al-Tawāṣul al-Adabī wa-al-Naqdī Unmūdhajān - Abd Alrahman Alsabet (Al-Ma‘rifah, 2019)
Arabic is one of the most important six languages ​​for which the UNESCO has designated an international day to celebrate. This increases its importance and makes it necessary for people to learn and adopt it as a means of communication. This research addresses the problem of language communication to identify effective methods for teaching the Arabic language in general and to speakers of other languages in particular. The research aims to identify the most effective methods that enhance language communication among peoples, especially in the field of literature and criticism, seeking to spread the language of the Koran worldwide. In Addition, it adopts the descriptive method by describing the most prominent methods that help in spreading the Arabic language all over the world. The research concluded that various methods can be utilized in spreading the Arabic language worldwide, the most important of which are the following: Poetry evenings that enrich language appreciation, public cultural meetings that focus on exchanging Arabic language topics, conferences and literary seminars for sharing language ideas, international exhibitions organized by government agencies and private institutions, especially international book fairs, and the social media; a quick and effective platform influencing the recipients.